The use of balloon breathing stimulation media to encourage students’ participation in learning science during the Covid-19 Pandemic - Jamalulail, Qodri; Nisa, Ana Fitrotun; Prihatni, Yuli; Saputra , Bherrio Dwi (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of the article is to describe improving the effectiveness of distance learning and the creative thinking of students to understand scientific concepts, especially human respiratory system material in grade V elementary school students. The implementation step: The preparation is the creation of an innovative lesson plan. The curriculum is designed to create a distance learning experience that stays active and creative. The learning process is done online through WhatsApp Group. Based on the distance learning that has been implemented, it can be concluded by using the media